Effects of ethanolic extract of Jasminum grandiflorum Linn. flowers on wound healing in diabetic Wistar albino rats - Hiren Hirapara; Vishal Ghori; Ashish Anovadiya; Seema Baxi; Chandrabhanu Tripathi (Mashhad University of Medical Sciences, 2017)
Objective: To evaluate wound healing activity of ethanolic extract of Jasminum grandiflorum Linn. (J. grandiflorum) flowers in diabetic rats. Materials and Methods: Streptozotocin-induced diabetic Wistar albino rats were divided into six groups (n=6).Three groups - diabetic control, positive control (that received Glibenclamide) and treatment (that received J. grandiflorum Linn. Flower extract) were operated for excision wounds (EW). These groups were evaluated for wound contraction and re-epithelization. The other three groups were operated for incision wounds (IW) and dead space wounds (DW). Incision and dead space wounds were produced in the same rats. IWs were analyzed for wound breaking strength and the granulation tissues from DWs were analyzed for dry weight, hydroxyproline content, and histology. Results: IWs and DWs showed significant improvement in wound breaking strength (265.8±10.4 vs 332.5±8.2; p